2018
DOI: 10.1002/ardp.201800123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer activity of novel rapamycin C‐28 containing triazole moiety compounds

Abstract: Rapamycin is an mTOR allosteric inhibitor with multiple functions such as immunosuppressive, anticancer, and lifespan prolonging activities. Its C-43 semisynthetic derivatives temsirolimus and everolimus have been used as mTOR targeting anticancer drugs in the clinic. Following our previous research on antitumor rapalogs modified on the C-43 position, 13 novel rapamycin triazole hybrids (6a-g, 7a-f) were designed and synthesized on the C-28 position of rapamycin via Huisgen's reaction.Anticancer assays indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Thus, N4 may have the potential to serve as a new mTOR inhibitor. C28 rapamycin-triazole N5 (IC 50 = 12.8–14.8 μ M) could also exert more potent inhibitory against A549, 769-P, ECA-109, and Caski cancer cells than rapamycin (IC 50 = 12.3–24.5 μ M) ( Huang Q. et al, 2018 ). Mechanistic studies indicated that N5 could inhibit the mTOR signaling by downregulating mTOR phosphorylation and its downstream key proteins such as P70S6K1 and 4EBP1.…”
Section: Click Chemistry-based Modification Of Macrocyclic Natural Productsmentioning
confidence: 99%
“…Thus, N4 may have the potential to serve as a new mTOR inhibitor. C28 rapamycin-triazole N5 (IC 50 = 12.8–14.8 μ M) could also exert more potent inhibitory against A549, 769-P, ECA-109, and Caski cancer cells than rapamycin (IC 50 = 12.3–24.5 μ M) ( Huang Q. et al, 2018 ). Mechanistic studies indicated that N5 could inhibit the mTOR signaling by downregulating mTOR phosphorylation and its downstream key proteins such as P70S6K1 and 4EBP1.…”
Section: Click Chemistry-based Modification Of Macrocyclic Natural Productsmentioning
confidence: 99%
“…Studies have reported 1,2,3-triazole derivatives with bactericidal [ 19 ] and anticancer [ 20 ] activity. These derivatives can induce cell cycle arrest and apoptosis of cancer cells [ 13 , 21 ].…”
Section: Introductionmentioning
confidence: 99%